Peran Penyuluh Pertanian dalam Penggunaan Combine Harvester di Kecamatan Purbolinggo Kabupaten Lampung Timur - Purnamawati, Tati; Gitosaputror, Sumaryo; Effendi, Irwan; Silviyanti S, Sherly; Listiana, Indah; Yanfika, Helvi (Journal of Food System & Agribusiness, 2023)
The use of Combine harvesters as an innovation in an effort to reduce yield loss does not always receive a good response. It is the job of the Agricultural Extension Officer, as a field implementer in the field of agriculture that is directly related, to devote all encouragement to farmers to be moved and able to change their way of thinking, work steps, and respond to innovation developments, especially the use of combine harvesters. The purpose of this research is to determine the role of agricultural extension workers in the use of combine harvesters. The research was conducted in Purbolinggo District, East Lampung Regency. The data in this study were taken in November 2021. The sample or respondents in this study consisted of 30 farmers in Purbolinggo District who were selected by purposive sampling. While the research method used is a survey, data analysis is done both descriptively and quantitatively. From the results of the research conducted, it shows that the role of agricultural extension workers as initiators, motivators, and facilitators is in the high category. In addition, there is a correlation between the role of the agricultural extension worker as an initiator, the role of the extension worker as a motivator, and the role of the worker as a facilitator on the quality, quantity of yield, time, cost, farmer's income, and environmental friendliness, except for the role of the extension worker as an initiator on the quality of the crops.